Correlações entre o índice BODE e variáveis máximas de esforço em pacientes com DPOC (Correlation between the BODE index and variables of maximal exercise capacity in patients with COPD) - Cavalheri, Vinicius; Mantoani, L.; Camillo, C.; Pitta, F. (Associação Brasileira de Fisioterapia Cardiorrespiratoria e Fisioterapia em Terapia Intensiva, 2016)
Background: Both the BODE index and the peak rate of oxygen uptake (VO 2 peak), one of the variables of maximal exercise capacity, are predictors of morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD). However, little is known about associations between the BODE index and variables of maximal exercise capacity. Objectives: To investigate correlations between variables of maximal exercise capacity and the BODE index in patients with COPD. Methods: Sixty patients with COPD (32 men), with forced expiratory volume in one second (FEV 1 ) 46 ± 16%predicted and age 66 ± 8 years underwent a maximal cardiopulmonary exercise test (CPET). During the CPET measures were collected of: maximum workload (Wmax), VO 2 peak, maximum minute ventilation (VEmax), maximal heart rate (HRmax), peripheral oxygen saturation at rest (SpO 2 rest), at the end of the test (SpO 2 end) and at recovery (SpO 2 rec). In order to characterize the population and calculate the BODE index, patients were also submitted to assessment of lung function (spirometry, with FEV 1 measurement), self-reported dyspnoea (Medical Research Council scale, modified version) and 6-minute walking distance. Pearson or Spearman correlation coefficients were used to verify possible associations. Results: The BODE index correlated with Wmax, VO 2 peak, VEmax, HRmax, SpO 2 rest, SpO 2 end e SpO 2 rec (-0.27 ≤ r ≤ -0.51; p≤0.05 for all). Regarding correlations amongst variables of maximal exercise capacity, the SpO 2 rest and SpO 2 rec correlated with VO 2 peak (r = 0.34 and 0.33, respectively; p=0.02 for both) and with the Wmax (r = 0.35 and 0.29, respectively; p=0.03). Conclusions: Better morbidity and mortality prognostic values, as measured by the BODE index, are moderately related to maximal exercise capacity, oxygen saturation and recovery after maximal stress.